2016
DOI: 10.1016/j.ncrna.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of dysregulated lncRNA expression in breast cancer cell identified by RNA-seq study

Abstract: Among all the sequencing techniques, RNA sequencing (RNA-seq) has galloped with pace adopting the profiling of transcriptomic data in almost every biological analytics area like gene regulation study, development biology and clinical research. Recently the discovery of differentially expressed genes across different conditions has outshone the barrier of genetic & epigenetic regulations. The present work identified and analyzed differentially expressed novel long non-coding RNAs (lncRNAs) for breast cancer. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Meanwhile, the function and mechanism of lncRNA in the development and prognosis of breast cancer have been increasingly emphasized [27]. Therefore, the in‐depth exploration of lncRNA has a very important role in the early diagnosis of breast cancer, including the search for potential biomarkers and the prognosis [28]. In the present study, we investigated lncRNA SOX21‐AS1 and found that the expression of SOX21‐AS1 in breast cancer was disordered.…”
Section: Discussionmentioning
confidence: 82%
“…Meanwhile, the function and mechanism of lncRNA in the development and prognosis of breast cancer have been increasingly emphasized [27]. Therefore, the in‐depth exploration of lncRNA has a very important role in the early diagnosis of breast cancer, including the search for potential biomarkers and the prognosis [28]. In the present study, we investigated lncRNA SOX21‐AS1 and found that the expression of SOX21‐AS1 in breast cancer was disordered.…”
Section: Discussionmentioning
confidence: 82%
“…CDKN2B-AS1 (ANRIL) is located in the 9q21.3 region with rs62560775, associated with lung adenocarcinoma and BC susceptibility [ 203 ]. CDKN2B-AS1 is upregulated in MCF10A breast epithelial cells [ 204 ] and in breast tumors [ 205 ]. CDKN2B-AS1 was identified as a member of the ceRNA network for MMP1/MMP11-miR-145-5p and speculated to be involved in the development of early BC [ 205 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tripathi et al. in their paper thoroughly described the integrated analysis of dysregulated lncRNAs, lnc-PCP4, and lnc-FAM in breast cancer expression using RNA-seq study [69] . In a parallel study done by a group of researchers from Scripps Research Institute, RNA seq data was analyzed to demonstrate region specific enrichment of populations of lncRNAs and mRNAs in the mouse hippocampus and pre-frontal cortex (PFC) which were found to be involved in memory storage and neuropsychiatric disorders [70] .…”
Section: Lncrna Profiling Using Rna-seq Analysis Toolsmentioning
confidence: 99%